Immediate Effects of Electro Acupuncture versus Laser Acupuncture on Pain and Disability in Women with Chronic Cervical Myofascial Pain Syndrome - Atefeh Bahadori Bozchelooee; Siamak Bashardoust Tajali; Zahra Fakhari; Monavar Hadizadeh (Journal of Modern Rehabilitation, 2022)
Introduction: Neck pain is the fourth leading cause of disability worldwide. This study aims to investigate the effects of Electro Acupuncture (EA) versus Laser Acupuncture (LA) on symptoms of women with chronic cervical myofascial pain syndrome. Materials and Methods: This is a single-blind randomized controlled clinical trial. Thirty women with chronic cervical myofascial pain syndrome were randomly divided into three groups: EA, LA, and sham. The EA group received electrical stimulation through needles at standard acupuncture points, while the LA group received low-intensity laser irradiation at the same points. The passive laser probe was applied for the sham group. The outcome measures were neck pain pressure threshold, neck pain severity, neck disability, and cervical range of motion Results: The pain severity and disability were significantly lower in the EA group than in the other two groups. The neck range of motion (cervical lateral flexion and rotation) and pain pressure threshold increased significantly in the EA group immediately and one week after the intervention. Conclusion: Both EA and LA interventions may be effective in alleviating the symptoms of cervical myofascial pain syndrome, but the EA can be more effective in reducing neck pain and disability in women with cervical myofascial pain syndrome.